“Evaluación física y sensorial de cuatro variedades de café (coffe arabica L.) Tolerantes a roya (Hemileia vastatrix), En relación a dos pisos eclógicos de la provincias de lamas y rioja” - Liliana estrella gamonal (2015)
The present research work entitled "assessing physical and sensory of four varieties of coffee (Coffea arabica L.) tolerant to rust (Hemileia vastatrix), in relation to two ecological floors of the provinces of Lamas and Rioja", was carried out in order to evaluate the physical characteristic of the fruit of the coffee, and sensory characteristics through wet mill, pulp removal by hand, natural fermentation and drying Sun. Sensory tests were conducted using a scale of 6-10 points (SCAA, 2005); to qualify each of the sensory attributes of varieties tolerant to rust from the provinces of Lamas and La Rioja: catuai, Caturra, Pache and Catimor as a witness by having Rust tolerant genes; in relation to two ecological floors: 800-1000 msnm and 1000-1200 msnm. For this we used a design completely at random (DCA) with 4 x 2 factorial arrangement, where the factors are variety and altitude, whose variables studied were: The physical characteristics of the fruit is length, width and thickness; in sensory characteristics are fragrance/aroma, flavor, residual flavor, acidity, body, evenness, balance, clean Cup, sweetness and score taster. The results obtained in this investigation, no significant differences in the interaction of variety and altitude were found, but no matter. The variety had greater influence on the physical characteristics of the fruit of the thickness variable (Sig.= 0.004), however, wide (Sig. = 0.175) and length (Sig. = 0.621) its measures are broadly similar between the varieties studied ; in sensory characteristics significantly influence fragrance I flavor (Sig = 0.006.), flavor (Sig = 0.006.), acidity (Sig = 0.0002.) and balance (Sig = 0.0001.); Likewise, the variety caturra excelled in the first two attributes with a rating of (7.55 and 7.35); 1 presenting sensory descriptors in fragrance / scent chocolates, citrus, fruit, mango, ripe banana, melon and fruity, light mandarin, melon, banana silk, plums; also excelled caturra variety of cup quality with a rating (82.1 O); however catimor scored the lowest rating in fragrance I flavor (7.10) presenting herbs sensory descriptors, to grains like nuts and other spices; also presented downgrades cup quality (80.23). In other attributes such as residual flavor, body, smoothness, sweetness, clean cup and score taster; practically similar scores presented varieties. The effect of altitude influenced the physical characteristic protruding further at higher altitudes in width (14.23) and thickness (13.70). In sensory characteristics, altitude improved fragrance I scent in obtaining a greater variety caturra cup quality rating (82.65), the highest one (1000-1200) msnm.